2023
DOI: 10.3390/su15129765
|View full text |Cite
|
Sign up to set email alerts
|

The Nexus of Corporate Affinity for Technology and Firm Sustainable Performance in the Era of Digitalization: A Mediated Model

Dharm Dev Bhatta,
Muddassar Sarfraz,
Larisa Ivascu
et al.

Abstract: This study aims to elaborate on the embeddedness of digital technology applications and their effect on firms’ sustainable performances under the mediating conditions of team innovation performance and digital organizational culture. The study employs a quantitative approach, and data were collected from 319 employees working in the information technology sector of China. Analyses of moment structures ((AMOS-version 27.0) and SPSS software- version 4.0) were used for data analysis, and the structural equation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 104 publications
1
6
0
Order By: Relevance
“…Research conducted by Lăzăroiu et al [185] indicated that organizations are more inclined to take risks due to the increased operational flexibility and accelerated procurement of financial resources induced by digital transformation. Instances of fraudulent activities can be diminished, and overall business quality can be improved through digital transformation [67]. Implementing digital trans-formation incentivizes businesses to adopt a more proactive stance towards environmental protection.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Research conducted by Lăzăroiu et al [185] indicated that organizations are more inclined to take risks due to the increased operational flexibility and accelerated procurement of financial resources induced by digital transformation. Instances of fraudulent activities can be diminished, and overall business quality can be improved through digital transformation [67]. Implementing digital trans-formation incentivizes businesses to adopt a more proactive stance towards environmental protection.…”
Section: Discussionmentioning
confidence: 99%
“…A positive link was observed between (a) the effectiveness and the performance of the company, (b) the alignment of the mission, consistency, and revenue, and (c) the adaptability, mission, and growth in sales. Participation, consistency, adaptability, and purpose are some factors that [67,68] found to impact organizations' performance. These aspects are interconnected with the processes of developing products, increasing sales, and maintaining quality, ultimately affecting the financial performance of companies.…”
Section: Corporate Sustainable Performance and Corporate Culturementioning
confidence: 99%
“…Green technology allows firms to earn more revenue by offering green products and services [ 81 ]. Green products occupy more market share than any other product [ 82 ]. It provides financial incentives to businesses, enabling the firms to save money and resources, thus acquiring GCA.…”
Section: Theoretical Background and Hypothesis Developmentmentioning
confidence: 99%
“…Another tool developed out of necessity during the COVID-19 pandemic has developed artificial intelligence platforms that adapt to students' learning styles, providing interactive and engaging educational content, thereby improving learning outcomes. Even after the period when learning was exclusively online, these platforms remained a frequently used tool, redefining traditional approaches to exams, academic conferences or school courses [42][43][44][45][46][47][48][49].…”
Section: Public Awareness Regarding the Benefits Of Aimentioning
confidence: 99%